Evaluation of motor transport legislation impact on passenger transportation safety - V. Yakunina, Natalja; N. Yakunin, Nikolaj; M. Menshikh, Olga; A. Dryuchin, Dmitri (International Journal of Engineering and Technology, 2018)
The article describes the issues regarding organization of passenger motor transport work. The purpose of the research was set, which consists in elaboration of theoretical and methodological regulations for safety assessment of motor transport legislation affecting passenger transportation. The description of theoretical and methodological instruments for assessment of motor transport legislation effect on passenger transportation safety was presented. Multi-level structure of motor transport legislation, resulting in excessive, not always efficient, variety of motor transport activities regulation, was shown. The analysis of regulation of organizational and functional structure indicators of transporters in motor transport legislation of regions’ located in the territory of Volga Federal District as of 2014 was carried out. The analysis of breakdown rate indicators was performed in passenger transport for the same period. Correlation analysis of those groups’ indicators was conducted. The obtained results indicate the existence of moderate negative relation between those groups’ indicators. An important scientific and practical task was solved, which consists in assessment of motor transport legislation affecting passenger transportation safety. It was ascertained that one of methods for managing the safety of passenger transportation by motor transport is regulation of organizational and functional structure of the transporters. The theoretical and methodological instruments were developed to purposefully improve the organization of and technology of passenger transportation by motor transport. There was an assumption made that an optimization of regulated requirements structure would eventually facilitate increase of safety of passenger transportation by motor transport. It was recommended to apply the results of this work in the course of transport legislation elaboration. There was the summary formulated. The conclusion of aim achievement and research hypothesis validity was made.